2023
DOI: 10.2478/mspe-2023-0015
|View full text |Cite
|
Sign up to set email alerts
|

Expectations for Renewable Energy, and Its Impacts on Quality of Life in European Union Countries

Abstract: The primary goals of the study are to present a qualitative examination of household awareness of renewable energy sources and to ascertain their requirements, as well as their expectations for an improvement in quality of life as a consequence of using renewable energy to reduce greenhouse gas emissions and air pollution while improving public health. There are no empirical studies examining the level of household awareness of renewable energy in EU countries, so this gap is also considered a further area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…The access of national producers to cheap renewable energy determines the future quality of life and the state of the environment, and this has been convincingly proven in a number of works, i.e., [25][26][27]. This Special Issue follows this trend; for example, in their article, A. Pacana, D. Siwiec, L. Bednárová, and J. Petrovský take environmental factors into account along with quality in modeling a product and its life cycle [28].…”
mentioning
confidence: 90%
“…The access of national producers to cheap renewable energy determines the future quality of life and the state of the environment, and this has been convincingly proven in a number of works, i.e., [25][26][27]. This Special Issue follows this trend; for example, in their article, A. Pacana, D. Siwiec, L. Bednárová, and J. Petrovský take environmental factors into account along with quality in modeling a product and its life cycle [28].…”
mentioning
confidence: 90%
“…Taking into account the type of renewable energy sources, the spatial approach and the time scope, it should be stated that this issue has not been definitively resolved [30]. Moreover, research shows that the awareness of households in EU countries regarding renewable energy sources and their requirements and expectations for improving the quality of life is low [31]. Other studies have indicated that the use of renewable energy sources is considered too expensive for low-income families to use this type of energy [32].…”
Section: Introductionmentioning
confidence: 99%